Distribusi Pesan Politik Calon Anggota Legislatif DPRD Partai Golkar Jakarta Barat Pada Pemilu 2024 - Poernomo, Marlinda Irwanti; Marentin, Caecilia (Jurnal Pustaka Komunikasi, 2025)
The Golkar Party, as one of the political parties in Indonesia, participating in the political process to put its candidates in legislative seats to represent the aspirations of the people in the 2024 elections. Political parties play an important role in the process of political communication, which aims to reach the various layers of society, including those who understand politics and those who don't. By communicating effectively, the political parties hope to prevent the spread of widespread political apathy among the public. The researchers learned about the success of the strategy of distribution of messages of the candidate legislative member of the DPRD party Golkar West Jakarta in the 2024 elections, as well as to find out the factors that shape and influence the distribution strategy of the messages of candidate parliamentary member of DPRD West Jakarta golkar party in the elections 2024 using qualitative research methods. Overall, the research finds that several strategies reflect a highly focused approach to direct and personal communication, with the potential to make greater use of digital platforms in the future. This analysis shows the importance of adaptation and flexibility in campaign message distribution strategies, which are in line with McNair's and McQuail's theories.